IMPACT OF EROSION PROCESS TO FERTILITY OFMOUNTAIN-CHERNOZEM SITUATING IN SOUTH-EAST SLOPE OF GREAT CAUCASIAN - Ali oglu, Soltanzade Gasim (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2018)
The complexity, sharp change in the relief condition, the tension of the anthropogenic factors in the Shamakhi region, where we have investigated, has intensified the erosion process. Because of the lack of agrotechnical measures on the slopes, the erosion process has been intensified, the soil is flooded with soil, the physical and chemical properties of the soil have deteriorated, the nutritional elements have declined, the vegetation has been degraded and reached the limit of destruction. For some reason, the object of research was Shamakhi two land cuts were set up to determine the degree of actual erosion of the soil in the village of Melam. which will result in preventive measures to prevent erosion intensities and to develop and implement appropriate preventive measures